2007
DOI: 10.3233/jad-2007-12306
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene Polymorphism and BPSD in Mild Alzheimer's Disease

Abstract: The purpose of the present study was to confirm an association of functional polymorphism within the serotonin transporter (5-HTT) gene with Alzheimer's disease (AD) and behavioral and psychological symptoms of dementia (BPSD) in mild AD. Apolipoprotein E (ApoE) gene polymorphism and 2 types of functional polymorphism in the 5-HTT gene, 5-HTTlinked polymorphic region (5-HTTLPR) and a 5-HTT variable number of tandem repeats sequence (5-HTTVNTR) were analyzed longitudinally in outpatients with mild AD to find ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…HTTLPR variants have been associated with depression (10), bipolar disorder (11), symptoms of Alzheimer's disease (12) and may act through a decrease in transcriptional activity of the gene in patients with the shorter allele (13). STin2 has been associated with schizophrenia (14), depression (15), symptoms of Alzheimer's disease (12,16) and treatment outcome in alcohol dependent patients (17). …”
Section: Introductionmentioning
confidence: 99%
“…HTTLPR variants have been associated with depression (10), bipolar disorder (11), symptoms of Alzheimer's disease (12) and may act through a decrease in transcriptional activity of the gene in patients with the shorter allele (13). STin2 has been associated with schizophrenia (14), depression (15), symptoms of Alzheimer's disease (12,16) and treatment outcome in alcohol dependent patients (17). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Cys23Ser polymorphism within the 5-HT2C receptor gene was significantly associated with visual hallucinations and hyperphagia in another sample of AD patients. In the same view, a 44-base pair insertion of the 5-HTTPRL gene was reported to be associated with psychosis and aggression [70][71][72][73][74], and a 5-HTT variable number of tandem repeats sequence, namely 5-HTTVNTR allele 10, was significantly related to the presence of BPSD or aggressiveness [75]. Further studies are needed [76].…”
Section: Genetic Basis Of Psychosis In Alzheimer Diseasementioning
confidence: 95%
“…This discrepancy may not be surprising since delusions are strongly related to the incidence of resistiveness to care that is often interpreted as "aggression" (6). Similarly, two studies found relationship between polymorphism of 5-HT transporter that may result in increased reuptake of 5-HT and "aggressive" behavior (19,20) while one study found relationship only with psychosis (21). The relationship between serotoninergic function and "aggressive" behavior may not be unique for AD because decreased serotoninergic modulation of the dopaminergic activity was correlated with "aggression" and agitation in frontotemporal dementia.…”
Section: Figurementioning
confidence: 95%